Development of an Elongational‐Flow Microprocess for the Production of Size‐Controlled Nanoemulsions: Application to the Preparation of Monodispersed Polymer Nanoparticles and Composite Polymeric Microparticles. Issue 1 (21st November 2016) - Yu, Wei; Serra, Christophe A.; Khan, Ikram U.; Er‐Rafik, Meriem; Schmutz, Marc; Kraus, Isabelle; Ding, Shukai; Zhang, Lixiong; Bouquey, Michel; Muller, René
Abstract : Composite polymeric microparticles doped with polymer nanoparticles are produced using a three‐step microfluidic procedure: elongational‐flow nanoemulsification of a monomer, polymerization of the nanodroplets, and emulsification of the resulting nanosuspension into microdroplets followed by the UV polymerization of the continuous phase. Abstract : A three‐step microfluidic process is proposed for the production of composite plain and Janus polymeric microparticles doped with polymer nanoparticles. These monodispersed microparticles are prepared by means of capillaries‐based microfluidic droplet generators from a dispersed phase obtained after the thermally induced or UV‐initiated miniemulsion polymerization of size‐controlled oil‐in‐water monomer‐based nanoemulsions produced in a novel elongational‐flow microemulsifier. Nanodroplets and polymer microparticles sizes are conveniently varied by tuning the different process parameters, namely, the reciprocating flow rate through the emulsifier microchannel and number of cycles for the former and flow rates of all immiscible phases for the latter. As such, 300 µm plain poly(acrylamide) microparticles and 400 µm poly(acrylamide)/doped poly(acrylamide) Janus microparticles containing 230 nm poly(tri(propylene glycol) diacrylate‐ co ‐methyl methacrylate) nanoparticles embedded selectively into one poly(acrylamide) domain are successfully prepared. This microfluidic process represents a facile route to the synthesis of multiscale and multidomain composite polymeric microparticles.